The International Tourism Activities: Modern Realities and Tendencies - Rakhman Mahbubur S.; Nahorna Yuliia V. (Bìznes Inform, 2019)
The article is concerned with the theoretical substantiation of the essence of international tourism and its significance, analysis of the main indicators of the economic development of the tourism industry of the world and Ukraine, exploration of the current tendencies and elaboration of a project of recommendations as to further development. The theoretical provisions on the essence of the term of «tourism» and the specifics of definition and functions of tourism are generalized; influence of the industry on the economy of a single country and the world is identified; the directions of applying management in the tourism industry and the structure of tourist product are considered. The authors analyze the international tourism indicators: contributions to GDP; volume of direct investments; share in total world exports and the exports of services; impact on employment and the dynamics of tourist flows in general and by the world regions. The structure of export revenues in the regional plane, ranking of the leading countries in terms of the volume of foreign visitors, and the volume of revenues from tourist exports in the dynamics are considered. A comparison of the species structure of the arrival of international tourists according to the purpose of travel is provided. An analysis of the main indicators of foreign trade in tourism services of Ukraine is carried out: number of subjects of tourist activities in terms of property and territorial accommodation; dynamics of the inbound and outbound tourist flow; advantages of foreign tourists as for the purpose of visiting Ukraine. The statistics on Ukraine’s foreign trade volumes on the item of article «travels» are analyzed. A project of recommendations as to improving the international tourism services is elaborated and conceived. The results are summed up and the current tendencies in the development of the world tourism are identified.